Characterization of bio-retted kenaf (Hibiscus cannabinus L.) bast fibre - Zalina Ya; Abu Bakar Sulong; Nabilah Afiqah Mohd Radzuan (Penerbit Universiti Kebangsaan Malaysia, 2024)
The bio-retted kenaf (Hibiscus cannabinus L.) bast fibres offer significant advantages over synthetic fibre regarding their being lightweight, environmentally friendly, and cheap. During the characterization procedure, the chemical composition as well as the physical, thermal, mechanical, crystallinity, and morphological properties of bio-retted kenaf (Hibiscus cannabinus L.) bast fibre were assessed. The chemical composition analysis of the bio-retted bast fibre of kenaf (H. cannabinus L.) revealed that it contained a significantly high proportion of cellulose (58.72%). While, in the tensile test, the bast fibre of bio-retted kenaf (Hibiscus cannabinus L.) exhibited an average tensile strength of 3876 ± 1122 MPa and modulus of elasticity of 577 ± 177 GPa. X-ray diffraction (XRD) analysis of the bio-retted kenaf (Hibiscus cannabinus L.) bast fibre revealed its crystalline size to be 19.65 nm and crystallinity index to be 68.62%. The thermogravimetric analysis (TGA) performed on the bast fibre of kenaf (Hibiscus cannabinus L.) revealed that it maintains a thermal stability of 240°C. The scanning electron microscope (SEM) was employed to examine the fibre’s morphology. The fibre exhibited flaws and a smoothed surface, as determined by the morphological evaluation. The utilisation of bio-retted bast fibre derived from kenaf (Hibiscus cannabinus L.) as a reinforcing agent in applications involving elevated temperatures exhibited encouraging outcomes.